Somewhat a trivial question, but I struggle to get my head around it. Consider we have an AR(1) process, as follows:

$y_t=\rho y_{t-1}+\varepsilon_t,\quad t=1,...,T$.

such that $\varepsilon_t$ are $i.i.d$ and $\varepsilon_t\sim N(0,1)$. Evidently, $y_t$ and $y_{t-1}$ are correlated and as such a joint probability, such as $P[y_t\leq0,y_{t-1}\leq 0]\neq P[y_{t}\leq 0]P[y_{t-1}\leq0]$.

But given that $y_t=\rho y_{t-1}+\varepsilon_t$ and $y_{t-1}=\rho y_{t-2}+\varepsilon_{t-1}$, the aforementioned joint probability can be manipulated and expressed as follows: \begin{eqnarray} P[y_t\leq0,y_{t-1}\leq 0]&=&P[\rho y_{t-1}+\varepsilon_t\leq 0,\rho y_{t-2}+\varepsilon_{t-1}\leq 0]\\ &=&P[\varepsilon_t\leq-\rho y_{t-1},\varepsilon_{t-1}\leq-\rho y_{t-2}] \end{eqnarray} But from earlier, we know that $\varepsilon_1,...,\varepsilon_t$ are $i.i.d$ implying that \begin{eqnarray} P[\varepsilon_t\leq-\rho y_{t-1},\varepsilon_{t-1}\leq-\rho y_{t-2}]&=&P[\varepsilon_t\leq-\rho y_{t-1}]P[\varepsilon_{t-1}\leq-\rho y_{t-2}]\\ &=&P[y_t\leq0][y_{t-1}\leq0] \end{eqnarray} which is obviously in contradiction with the earlier results. I know I am missing a step here, so some clarification would be very much appreciated.

  • $\begingroup$ The conclusion after "implying that" appears to assume $y_{t-1}$ and $y_{t-2}$ are independent of each other and of $\varepsilon_t$ and $\varepsilon_{t-1}.$ Is that the case? If not, what is your justification for it? $\endgroup$ – whuber Nov 15 '19 at 0:17
  • $\begingroup$ I am rather confused. Clearly in and AR(1) process, $y_1$ and $y_2$ are not independent. Hence, as mentioned earlier $P[y_{t-1}\leq 0,y_{t-2}\leq 0]\neq P[y_{t-1}\leq 0]P[y_{t-2}\leq 0]$. However, my point is if the inequalities in the joint probability are expressed in terms of the residuals, and we already know that the residuals are independent, then $P[\varepsilon_{t}\leq -\rho y_{t-1},\varepsilon_{t-1}\leq -\rho y_{t-2}]=P[\varepsilon_{t}\leq -\rho y_{t-1}]P[\varepsilon_{t-1}\leq -\rho y_{t-2}]$. Is that not the case? Or is my question still ambiguous? $\endgroup$ – Carl Nov 15 '19 at 0:25
  • 1
    $\begingroup$ @Carl: in your $\epsilon$ equation, rhs of the inequality is not a constant but a random variable itself, so just because LHS is iid you cannot split it as you have. $\endgroup$ – Dayne Nov 15 '19 at 2:26
  • $\begingroup$ @Dayne What do you exacly imply by not splitting? So suppose you have expressed $P[y_{t-1}\leq0,y_{t-2}\leq0]$ in terms of residuals as I have. Do you imply that if I were to express the probabilities as bivariate normal CDFs, the covariance matrix should contain non-zero off-diagonal elements (i.e. implying correlation of the residuals)? $\endgroup$ – Carl Nov 15 '19 at 3:33
  • 1
    $\begingroup$ @Carl let me put it this way: let $A, B, C, D$ be four random variables such that $A, B$ are independent and $C, D$ are not. Clearly, $Pr(A<a, B<b)=Pr(A<a)Pr(B<b) \forall a,b \in \mathbb R$. However, do you think the following is also true? $Pr(A<C, B<D)=Pr(A<C)Pr(B<D)$. I think not as now your random variables become $A-C$ and $B-D$ which are not independent. $\endgroup$ – Dayne Nov 15 '19 at 4:55

Assuming a fixed initial value $y_0\in\mathbb R$, we have $y_t = \rho^t y_0 + \sum_{i=1}^t\rho^{i-1}\varepsilon_t$ for $t=1,2,\ldots,T$. Note that the linear combination of independent normal random variables is again normal, so $\sum_{i=1}^t\rho^{i-1} \varepsilon_t$ has $N\left(0,\frac{1-\rho^{2(t-1)}}{1-\rho^2}\right)$ distribution. For any $t\in\{1,2,\ldots,T\}$ we may compute the joint distribution of $(y_t,y_{t-1})$ by \begin{align} \mathbb P(y_t\leqslant u, y_{t-1}\leqslant v) &= \mathbb P\left(\rho^ty_0 + \sum_{i=1}^t \rho^{t-i}\varepsilon_i\leqslant u, \rho^ty_0 + \sum_{i=1}^{t-1} \rho^{t-i}\varepsilon_i \leqslant v\right)\\ &= \mathbb P\left(\sum_{i=1}^t \rho^{t-i}\varepsilon_i\leqslant u-\rho^ty_0, \sum_{i=1}^{t-1} \rho^{t-i}\varepsilon_i\leqslant v-\rho^ty_0, \right)\\ &= \mathbb P\left(\varepsilon_t+ \sum_{i=1}^{t-1} \rho^{t-i}\varepsilon_i\leqslant s-\rho^ty_0, \sum_{i=1}^{t-1} \rho^{t-i}\varepsilon_i\leqslant v-\rho^ty_0 \right). \end{align}


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.